An Unusual Case of Wart-like Presentation of Ocular Surface Squamous Neoplasia - Shrestha, Nirsara; Shrestha, Sangeeta; Shrestha, Arjun (Nepalese Medical Journal, 2019)
The ocular surface squamous neoplasia refers to the entire spectrum ranging from mild to severe dysplasia to carcinoma in situ and invasive squamous cell carcinoma. Ocular surface squamous neoplasia may present clinically in various ways: gelatinous, velvety or papilliform or leukoplakic. This case report describes a 50-year-old male who presented with a filiform wart-like appearance of conjunctival mass unlike described earlier. Excisional biopsy was done and histopathology revealed intraepithelial neoplasia with high-grade dysplasia.